Effects of Irisin on the Reproductive System of Obese Female Rats Induced by a High-fat Diet - Ertugrul, Nazife Ulker; Yardimci, Ahmet; Tektemur, Nalan Kaya; Bulut, Ferah; Ozcan, Mete; Kelestimur, Haluk; Canpolat, Sinan (Univ Ljubljana, 2024)
Obesity is becoming more common all across the world, causing a variety of health problems, including reproductive disruption. Although the novel, exercise -induced hormone irisin may affect the hypothalamus -pituitary -gonadal axis and reproductive function control, its impact on obesity -induced damage to the female reproductive system is not fully known. Hence, this study aimed to investigate the potential effects of irisin on reproductive hormones and reproductive organs in female rats with obesity induced by a high -fat diet. Forty female rats were divided into four groups: control, irisin, obese, and obese+irisin (n = 10 in each group). After simulating a high -fat diet -induced obesity model (via 60% kcal fat for 12 weeks) in the obese and obese+irisin groups, irisin (100 ng/kg/day via mini -osmotic pumps for about 28 days) was administered subcutaneously to the irisin and obese+irisin groups. Results showed that subcutaneous irisin perfusion increased serum luteinizing hormone (LH), the LH to follicle -stimulating hormone (FSH) ratio (LH/FSH), and progesterone levels while decreasing the histopathological damage in the ovaries of obese rats. On the other hand, endogenous irisin serum concentrations were similar in lean female rats and obese female rats with reproductive disorders. These results suggest that irisin may affect the reproductive axis in obese female rats. An increase in serum LH levels, which trigger ovarian steroidogenesis, and reducing histopathological changes in ovarian tissue could contribute to this effect.
U?inki irisina na reproduktivni sistem debelih samic podgan, povzro?eni s prehrano z visoko vsebnostjo maš?ob
Keywords: irisin; obesity; hormones; ovary; apoptosis; female reproduction